Rescue of the Mucocutaneous Manifestations by Human Cord Blood Derived Nonhematopoietic Stem Cells in a Mouse Model of Recessive Dystrophic Epidermolysis Bullosa. (21st May 2015) - Liao, Yanling; Ivanova, Larisa; Zhu, Hongwen; Yahr, Ashlin; Ayello, Janet; van de Ven, Carmella; Rashad, Ahmed; Uitto, Jouni; Christiano, Angela M.; Cairo, Mitchell S.
Abstract : Recessive dystrophic epidermolysis bullosa (RDEB) is a severe skin blistering disease caused by mutations in COL7A1 ‐encoding type VII collagen (C7). Currently, there is no curative therapy for patients with RDEB. Our previous studies demonstrated that human umbilical cord blood (HUCB) derived unrestricted somatic stem cells (USSCs) express C7 and facilitate wound healing in a murine wounding model. The primary objective of this study is to investigate the therapeutic functions of USSCs in the C7 null ( Col7a1 −/− ) C57BL6/J mice, a murine model of RDEB. We demonstrated that intrahepatic administration of USSCs significantly improved the blistering phenotype and enhanced the life span in the recipients. The injected USSCs trafficked to the sites of blistering and were incorporated in short‐term in the recipients' skin and gastrointestinal tract. Consistent with an overall histological improvement in the epidermal‐dermal adherence following USSC treatment, the expression of C7 at the basement membrane zone was detected and the previously disorganized integrin α6 distribution was normalized. We also demonstrated that USSCs treatment induced an infiltration of macrophages with a regenerative "M2" phenotype. Our data suggest that HUCB‐derived USSCs improved the RDEB phenotype through multiple mechanisms. This study has warranted future clinical investigation of USSCs as a novel and universal allogeneic stem cell donor source in selected patients with RDEB. Stem Cells   2015;33:1807–1817